BRRI-IRRI Collaborative Sustainable Intensification of the Mixed Farming System (SI-MFS) Activities and Outputs in 2023 - Khatun, Amina; Ahmed, S.; Bhandari, Humnath (International Rice Research Institute, 2023)
Objectives: - Collaboration with Bangladesh Rice Research Institute to conduct rice-based cropping systems intensification and diversification research. - Scaling of diversified and intensified cropping systems. - Testing climate-smart and resource-conserving rice production technology.